Characterisation of industrial potato waste for suitability in food applications. (24th August 2022) - Singh, Lovepreet; Kaur, Sukhpreet; Aggarwal, Poonam; Kaur, Navjot
Summary: The present study aimed at exploring different properties of industrial potato waste for their possible utilisation in various food formulations as a functional ingredient. Potato waste (potato peel and mash) was processed into powders and studied for various biochemical, technological, and morphological characteristics. Analysis of potato mash powder exhibited high techno‐functional potential as water absorption capacity (4.11 g/g) and swelling capacity (4.84 cm 3 /g) while peel powder showed high crude fibre (13.05%), protein (13.15%), and mineral content along with bio‐functional attributes (834.24 mg GAE/100 g total phenolics and 247.18 mg QE/100 g flavonoids) which were further verified using HPLC and FTIR analysis. Colour coordinates showed darker colour of potato peel compared to mash powder. SEM micrographs of PMP revealed the presence of native starch granules while the presence of cellulose structure was confirmed in peel powder. Storage studies of waste powders revealed shelf stability of 6 months, indicating their high potential for valorisation. Abstract : Characterisation of industrial potato waste